Under Threat: The Use of Recruitment Agents in the United States - Altbach, Philip; Reisberg, Liz (International Higher Education, 2022)
Recently, the US Congress passed a law that inadvertently could have turned the use of agents for recruiting international students into an illegal activity. Many universities rely on agents and recruiters. This article discusses the “crisis“ and argues that agents should in any case not be used.